Determining Staffing Needs for the Office of the Registrar at Visayas State University- Isabel Campus - Diano, Simon Peter; Lucero, Fritzie (Journal of Interdisciplinary Perspectives, 2025)
The Registrar's Office at Visayas State University-Isabel Campus faces significant challenges due to understaffing, resulting in various work-related issues. This study determines the appropriate staffing needs to address these challenges and enhance office efficiency and effectiveness. A comprehensive work sampling study was conducted, collecting 1,225 observations over ten days from five staff members. Results indicated that staff productivity percentages exceeded the normal range of 70-75%, emphasizing the need for additional personnel to address excessive workload and mitigate associated risks. Two techniques—fractional manpower computation and workload analysis—were employed to determine optimal staffing requirements. Analysis revealed a fractional manpower value of 6.325, indicating that six staff members are necessary, considering fractional manpower cut-off values. The workload analysis corroborated this finding, ensuring an average workload of 95.04%, well below the 100% limit. The study concludes that the Registrar's Office should increase its staff from five to six individuals to achieve optimal functioning. This adjustment will significantly improve workload distribution and overall efficiency. The findings provide valuable insights for informed decision-making regarding personnel allocation in similar administrative settings, offering considerable practical implications for organizational management.